Respuesta a diferentes niveles de fertilizantes foliares en el cultivo de arroz (Oryza sativa, L), en condiciones de secano, en la zona de Babahoyo - Rodríguez Guayes, Christian Marcelo (2019)
This experimental work was carried out on the grounds of the Sofia Farm, located at km, 13 of the Babahoyo-Montalvo road: “May 24” Campus; with geographical coordinates of 79º18´ of West Longitude and 1º47´ of south latitude, and with a height of 12 m,s,n,m, The rice variety INDIA SFL -11 was used as planting material, The treatments consisted of four applications of foliar fertilizer lines, in general doses of 1,5 and 2,0 kg / ha for the different lines applied, The frequency of application was 15 days respecting the functionality of the products, An absolute witness was integrated without application, The experimental design Randomized Blocks with five treatments and 4 repetitions was used, the significance test used was Tukey at 95% probability, All the necessary agricultural work was carried out in the cultivation of rice for its normal development such as soil preparation, planting, irrigation, fertilization, weed control, phytosanitary control and harvest, To estimate the effects of the treatments, the following data were taken: plant height, number of tillers, number of panicles, length of panicles, grains per panicle, weight of 1000 grains, yield, economic analysis, From the results obtained, it was determined that the foliar fertilizers applied in treatments T1 and T2 showed statistical differences in height with respect to the control T5 without application, The T3 treatment reacted better than the T1, T2, T4 and T5 treatments with grains per panicle, In the weight of 1000 grains the treatments T2 and T3, obtained a significant difference with respect to the rest of the treatments, The best performance we had was T1, where we reached 6015,88 kg / ha, Through the economic analysis it was found that the best economic performance we had with the T1 treatment with $ 933,35,